2020
DOI: 10.3390/ijerph17134904
|View full text |Cite
|
Sign up to set email alerts
|

Shock Index: A Simple and Effective Clinical Adjunct in Predicting 60-Day Mortality in Advanced Cancer Patients at the Emergency Department

Abstract: Deciding between palliative and overly aggressive therapies for advanced cancer patients who present to the emergency department (ED) with acute issues requires a prediction of their short-term survival. Various scoring systems have previously been studied in hospices or intensive care units, though they are unsuitable for use in the ED. We aim to examine the use of a shock index (SI) in predicting the 60-day survival of advanced cancer patients presenting to the ED. Identified high-risk patients and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 43 publications
1
12
0
1
Order By: Relevance
“…Even when detailed records of cancer patients’ clinical progression and treatment history were made available, physicians could predict 180-day mortality accurately only three out of four times [ 14 ]. With comparable accuracy rates of 73.11% in our retrospective study and 66.10% in this current validation study, SI is therefore a powerful risk stratification tool for rapid prognostication of 60-day mortality in advanced cancer patients presenting to the ED [ 18 ].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Even when detailed records of cancer patients’ clinical progression and treatment history were made available, physicians could predict 180-day mortality accurately only three out of four times [ 14 ]. With comparable accuracy rates of 73.11% in our retrospective study and 66.10% in this current validation study, SI is therefore a powerful risk stratification tool for rapid prognostication of 60-day mortality in advanced cancer patients presenting to the ED [ 18 ].…”
Section: Discussionmentioning
confidence: 83%
“…If advanced cancer patients presenting to the ED are unlikely to survive past 59 days, it then stands to reason that they should be provided early with the option of palliative care services. Based on this, we embarked on a retrospective study that found shock index (SI) to be an ideal tool in predicting the 60-day mortality risk of advanced cancer patients presenting to the ED [ 18 ]. SI is defined as the ratio of pulse rate to systolic blood pressure [ 19 ] and has been widely studied in the prognostication of pneumonia [ 20 , 21 , 22 ], influenza [ 23 ], Coronavirus disease 2019 [ 24 ], acute pulmonary embolism [ 25 ], acute myocardial infarction [ 26 , 27 ], stroke [ 28 ], and trauma [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 24 ] Some studies have shown that LR is effective in analyzing mortality factors and predicting mortality. [ 25 , 26 ]…”
Section: Methodsmentioning
confidence: 99%
“…Two studies identified factors of survivorship of palliative care patients using data from routine records. Cheng and colleagues [ 5 ] used data from the medical records of 305 patients with advanced cancer attending the Emergency Departments of three hospitals in Taiwan, showing the strong predictive power of a simple index, named the Shock index (pulse rate/systolic blood pressure), in predicting 60-day survival rate. Kawakami and Hamano [ 6 ] analyzed data from 106 residents with moderate-to-severe impairment of activities of daily living (ADL) and cognitive frailty in a nursing home in Japan, showing that change in body mass index, energy intake, and fluid intake were prognostic factors for death.…”
Section: Included Workmentioning
confidence: 99%